Pengaruh Kompetensi Pedagogik Guru terhadap Motivasi Belajar Siswa - Rini Andini; Haeril Haeril; Hamka Hamka (Journal on Education, 2025)
This research is quantitative research with an ex post facto design. The research location was at SMA Negeri 15 Bone with a sample of eye teachers who taught class XI IPS (social sciences) and class XI IPS students. Data collection techniques use observation, documentation and questionnaires, followed by data analysis using validity tests, reliability tests and hypothesis tests using simple linear regression equations and t tests. The results of the research using a questionnaire, validity test on variable For variable Y, the lowest value is 0.000>0.05 and the highest value is 0.046. The variable reliability test (X) alpha value is 0.814, meaning it is very reliable. Meanwhile, in the variable reliability test (Y). The alpha value is 0.570 with quite reliable results. In the hypothesis test, the consistency value is 97.694, it can be concluded as a constant number based on the results of the output value, the significant value is 0.011, more than the probability value of 0.05, so the result obtained is that H1 is accepted. In the t test, it is 1782. So it can be concluded that the calculated t value is more than t table or (2.992 > 1.782. There is a significant influence.